Dynamic pore structure evolution of the ion adsorbed rare earth ore during the ion exchange process - Zhou, Lingbo (R Soc Open Sci, 2019)
During the leaching process of the ion-adsorbed rare earth (RE) ore, the pore structure evolution of the ore body plays a vital role in the seepage of the leaching solution. To investigate the evolution of the pore structure during the leaching process, experiments have been carried out with remodelled RE ore samples based on the physical characteristics of in situ ores. The seepage rate difference between deionized water leaching solution and 2% NH(4)Cl leaching solution during the active leaching period was analysed. The porosity and the dynamic pore size evolution of pore structures in the ore body are discussed. Results indicate that along with ion exchange between the RE ore and the leaching solution, the porosity of the sample remains constant and the pore structure shows a decreasing trend in the first part and an increasing trend in the second part. Specifically, during the ion exchange process, the number of minimal pores (0–5 µm), small pores (5–10 µm) and medium pores (10–25 µm) increases significantly and the number of medium–large pores (25–60 µm), large pores (60–120 µm) and mega pores (greater than 120 µm) decreases dramatically. Along with the completion of the ion exchange process, the evolution of porous structure shows an opposite trend. The mechanism study reveals that the evolution of pore structure is induced by the difference of ionic strength in the leaching solution during the ion exchange process, where the RE ore microparticles will be absorbed or desorbed on to the solid phase.